2002
DOI: 10.1203/01.pdr.0000032071.90497.50
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in Breast Tissue Size in Infancy: Correlation with Serum Estradiol

Abstract: Breast tissue in newborn infants is considered to be physiologic and mainly related to exposure to maternal hormones in utero or through breast-feeding. However, controversy exists as to whether breast tissue in later infancy is under the influence of endogenous hormones. Children at 2-4 mo of age have a surge of reproductive hormones, including estradiol, which may affect the mammary gland. In a prospective cohort study of 1126 healthy, 3-mo-old infants, breast tissue size and reproductive hormones were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…4 Furthermore, different investigative methods in the literature have contributed to results that are not comparable. 7 Palpable breast tissue was found to be a common physiological phenomenon in our study subjects of both genders, though more commonly in females (present at 83.8% of female visits compared to 75.2% of male visits). The percentage of those with palpable tissue and breast tissue size declined with age, and after 10 months, the 50 th percentile for breast unit size in males was nearly zero.…”
Section: Discussionmentioning
confidence: 60%
“…4 Furthermore, different investigative methods in the literature have contributed to results that are not comparable. 7 Palpable breast tissue was found to be a common physiological phenomenon in our study subjects of both genders, though more commonly in females (present at 83.8% of female visits compared to 75.2% of male visits). The percentage of those with palpable tissue and breast tissue size declined with age, and after 10 months, the 50 th percentile for breast unit size in males was nearly zero.…”
Section: Discussionmentioning
confidence: 60%
“…Animal studies have shown that elevated estradiol levels may prolong atrial effective refractory periods (28) and differences in estradiol concentrations between the genders in infants have been observed (29). It is thus conceivable that prenatal differences in such hormone levels in association with gender and growth retardation may lead to the observed differences in atrial conduction observed here.…”
mentioning
confidence: 67%
“…All pregnant women of Danish origin, geographically belonging to the hospital referral area, and not referred because of expected complications in pregnancy, were consecutively recruited during their first trimester. The children were part of an ongoing comprehensive cohort study investigating kidney size and malformations, genital development and malformations, and general body growth [10,11,12].…”
Section: Methodsmentioning
confidence: 99%